Fistula Arteri Koroner, Penyebab Nyeri Dada yang Jarang Ditemukan pada Dewasa : Peran Computed Tomography Angiografi - Prima Almazini; Andy Rahman; Dian Yaniarti; Elen Sahara; Celly Anantaria; Manoefris Kasim (The Indonesian Heart Association, 2015)
Coronary artery fistula, usually congenital in origin, is an abnormal communication between a coronary artery and a cardiac chamber or great vessel. A coronary artery fistula can produce myocardial ischemia from coronary steal phenomenon. First case, a 54-year-old man was found to have a fistula from the left anterior descending coronary artery and right coronary artery to the main pulmonary artery, a rare anomaly. This patient developed chest pain due to myocardial ischemia in the left anterior descending coronary artery distribution for several months before evaluation. The patient was suggested to close the fistula but rejected. Second case, a-57 year-old woman was found to have fistula from left anterior descending coronary artery to main pulmonary artery. Patient presented with chest pain since 6 years ago. The patient was planned to close the fistula transcutaneously. Coronary artery fistulas, though rare, should be considered in the differential diagnosis when an adult patient presents with chest pain. Although coronary angiography is the gold standar diagnostic test for detection of coronary artery fistula, computed tomography angiography may be an alternative test through its good spatial resolution.